PELAYANAN BAGI ANAK KORBAN KEKERASAN SEKSUAL (Studi di DKI Jakarta) - Susilowati, Ellya; Ratnaningrum, Sri (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2023)
The Convention on the Rights of the Child (CRC ) states that children who are victims of sexual violence have the right to receive special protection and recovery services so that it does not cause trauma and disrupt the child's mental health. This research aims to get an overview of services for child victims of sexual violence in DKI Jakarta. This research uses a qualitative approach to understand in depth the service process for child victims of violence carried out by government institutions, namely the Handayani Center and local governments, especially in DKI Jakarta, namely P2TP2A. Data collection techniques were carried out using interviews, Focus Group Discussions (FGD) with service providers and officers, observations of the service process and documentation studies in case reports. The informants for this research are service officers (hot line service, caregivers, and social rehabilitation), children's social workers (Sakti Peksos) as companions. Research results show that the Handayani Center under the Ministry of Social Affairs during 2022 has provided social rehabilitation for 8 children who are survivors of sexual violence, and the DKI Jakarta UPTD P2TP2A also handled 120 children. The rehabilitation service process has referred to the standards outlined by WHO, however there is still a need to improve services related to monitoring to ensure children are mentally healthy and can continue their child development tasks.